Antimalarial flavonoid glycoside from Carica papaya with inhibitory potential against Plasmodium falciparum dihydrofolate reductase thymidylate synthase: an in-silico study - Sri Laksemi, Dewa Ayu Agus; Primayanti, I Dewa Ayu Inten Dwi; Surudarma, I Wayan; Damayanti, Putu Ayu Asri; Susanti, Ni Made Pitri (Faculty of Medicine, Universitas Trisakti, 2025)
BACKGROUNDCarica papaya is traditionally used to treat malaria. The mechanism of action of the active constituents may be determined by molecular docking. This study therefore examined the in silico antimalarial activity of selected compounds from Carica papaya using Plasmodium falciparum dihydrofolate reductase thymidylate synthase (PfDHFR-TS) as target protein. METHODSAntimalarial activity screening of Carica papaya compounds was done in silico using AutoDock 4.2 software which was equipped with Autodock tools 1.5.6 for preparation. Five compounds contained in Carica papaya leaves, i.e. quercitrin, isoquercitrin, carpaine, caricaxanthin, and violaxanthin were successfully docked with the target protein. The molecular docking method is declared valid if the RMSD obtained is not more than 2 Å. In vitro evaluation of the test compounds as antimalarials was accomplished by determining their inhibitory activity against dihydrofolate reductase thymidylate synthase (PfDHFR-TS) which plays a role in the synthesis of nucleotides needed by Plasmodium falciparum. RESULTSValidation of Plasmodium falciparum DHFR-TS with PDB ID 1J3I showed an RMSD value of 1.58 Å. The docking results showed that quercitrin, isoquercitrin, carpaine, and caricaxanthin showed negative energy values similar to the native ligand. Therefore the four compounds have good affinity for the target protein, while violaxanthin shows a positive energy value, indicating no affinity for the target protein. CONCLUSIONBased on binding affinity values and molecular interactions, isoquercitrin and quercitrin have inhibitory activity against dihydrofolate reductase thymidylate synthase (PfDHFR-TS), such that they have potential as natural antimalarial candidates.